Enhancing High School Geography Learning through a TikTok-Based E-Module on Flood Disaster Mitigation - Budiati, Roisyah; Suharini, Erni; Kurniawan, Edi; Santoso, Apik Budi (Jurnal Pendidikan Progresif, 2025)
Enhancing High School Geography Learning through a TikTok-Based E-Module on Flood Disaster Mitigation. Objective: The research aims to accomplish the following objectives: to compile design and feasibility, to explain the learning process, to determine the influence, and to provide an evaluation of the learning effectiveness. Methods: Techniques for quantitative data analysis were utilized in the research and development part of the methodology. A needs analysis, drafting, gathering references, assembling media, and evaluation are some of the findings that emerged from the study undertaken for the design compilation. There are three stages that make up the learning process: planning, implementation, and evaluation. Findings: The results of the students' learning on the pre-test (38%) and the post-test (79%) demonstrate the impact that the use of e-modules and videos from TikTok has had on their understanding. It can be concluded that the e-module media for flood catastrophe mitigation based on TikTok videos has an effect on the learning outcomes of students, as indicated by the mean result of 0.001. The n-gain test of the control class yielded a result of 31.1, which indicates that the class is considered ineffectual. It is determined that the experimental class has an n-gain of 56.4, which is considered to be extremely effective. Because of this, the use of e-module media for the mitigation of flood disasters based on videos from TikTok is more effective than the utilization of module media and films from YouTube. Conclusion: The conclusion is that the e-module for flood catastrophe mitigation that is based on videos from TikTok should be utilized more frequently as a source for studying geography. This is due to the fact that YouTube videos have been shown to be helpful in boosting learning outcomes. Keywords: tiktok-based e-module, Flood disaster mitigation, geography learning.